Schoolscaping in a Multilingual Area: An Example of a Hungarian College in Western Ukraine - Váradi Krisztián; Hires-László Kornélia; Máté Réka (Darnioji daugiakalbystė)
Transcarpathia is one of the westernmost counties of Ukraine with a century-long multilingual tradition. The biggest minority group in the region is formed by Hungarians whose main educational and cultural centre is the Ferenc Rákóczi II Transcarpathian Hungarian College of Higher Education. The linguistic landscape of the region has been analysed several times, but the same cannot be said about schoolscape studies. Therefore, the present paper aimed to solve this research gap and investigate how a minority higher education institution can implement current educational and language policies in its linguistic landscape. The study employed a qualitative approach to show the symbolic significance of the languages used in an educational setting. Altogether 394 pictures were taken in the corridors of the main building of the Transcarpathian Hungarian College, in the Philology Campus, in several classrooms, and in the near environment of the institution. The pictures were divided into eight distinct categories, ranging from bottom-up to top-down initiatives: decorations, symbolic inscriptions, advertisements, instructions related to crises, names of rooms, educational documents, library signage, and other signs and announcements. In addition, the official website and the social networking sites of the Transcarpathian Hungarian College were analysed briefly as part of a virtual schoolscape analysis. Based on the results, the Rákóczi College follows a strong bilingual tradition by making everything available in at least two languages (Ukrainian and Hungarian), but the bottom-up domain is also subject to monolingualism. Furthermore, the online schoolscape of the institution is multilingual because everything is published in three languages (Ukrainian, Hungarian, and English). The research can be further expanded with the help of the aforementioned qualitative approach of schoolscaping in other Transcarpathian Hungarian educational institutions to get a deeper insight into the applied multilingual practices in a war-torn country.